Movement variability in Pilates: a scoping review - Pereira, Mário José; Dias, Gonçalo; Mendes, Rui; Martins, Fernando; Gomes, Ricardo; Castro, Maria António; Vaz, Vasco (Frontiers in Psychology, 2023)
Objective This scoping review aimed to identify studies that analyzed movement variability in Pilates. Following a systematic approach to mapping evidence on this topic would highlight concepts, theories, sources, and knowledge gaps in this area. Methods This review used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) criteria for the selection, reading, and analysis of studies in this area. We searched five literature databases (Web of Science, SCOPUS, library catalog of the Faculty of Sport and Physical Education of the University of Coimbra—EBSCO Discovery Services, MEDLINE, and Google Scholar). Eligible articles contained the word “Pilates,” and the human movement variability was analyzed. Any type of study (except reviews) could be eligible and must have been published between 1 January 2002 and 30 November 2022, in Portuguese, Spanish, French, or English. Results Our search identified five eligible entries. Only one study used the Pilates method in its intervention, pointing to a more significant variability of hip–knee coordination, suggesting more diversified coordination patterns, and maintaining the variability of the angular position of the joint. Conclusion Very few studies have examined movement variability in Pilates, and only one applied an ecological framework.